Improving Literacy Outcomes for At-Risk Kindergartners through an Afterschool Tutoring Program: Results from a Feasibility Study - Pelatti, Christina Yeager; Piasta, Shayne B. (Frontiers in Education, 2017)
Background: Students from low-income backgrounds are at-risk for academic difficulties. Although a considerable number of students from this population attend community-based afterschool programs, little is known about their effectiveness in promoting academic learning. The purpose of this feasibility study was to examine the impact of an afterschool tutoring program on the literacy skills of kindergartners and youth from low-income homes. Method: This study incorporated a quasi-experimental pre-posttest design that included 10 kindergartners and 13 youth who participated in the program and a comparison group of 10 kindergartners. Following completion of an assessment battery, kindergartners and youth read in dyads for 10 weeks after which they were re-assessed on the same measures. Results: Kindergartners who participated in the program had significantly greater gains in phonological awareness as compared to the comparison group. Although participants described that the program was beneficial, no other comparisons on scores for kindergartners or youth reached statistical significance. Conclusions: These results provide evidence that this brief, low-cost program may have a positive effect on aspects of participants’ reading skills. This is one avenue that may narrow the achievement gap for at-risk students, although additional research is warranted. These findings support that providing students from at-risk backgrounds with experiences that target academic skills, specifically literacy, outside of the traditional school context may enhance educationally relevant learning.